Children's mathematics : making marks, making meaning - Carruthers, Elizabeth (SAGE, 2006)
"I purchased a copy of your book over the holidays-it is my bebtime reading at the moment but it is far too stimulating'- Philippa Cook, Nursery Teacher, Clifton High School, Bristol. 'Thought-provoking and inspirational throughout. If you want to expand your understanding upwards and outwards then get a copy soon"--John Dabell, Education Consultant, Former Numeracy Consultant & Ofsted Inspector. Praise for the First Edition : ' Children's Mathematics: Making Marks, Making Meaning is essential reading for students of Education and Early Childhood Studies, as well as for those practitioners w.- Resumé vydavatel